The effect of physical activity on the knee joint: is it good or bad? - Urquhart, D. M.; Wluka, A. E.; Teichtahl, A. J.; Cicuttini, F. M. (British Journal of Sports Medicine, 2007)
Could the promotion of physical activity inadvertently increase the burden of osteoarthritis? The promotion of physical activity is a major public health initiative in developed countries world wide. Although physical activity protects against a large range of health conditions, including cardiovascular disease, obesity and osteoporosis, it is unclear whether physical activity increases the risk of osteoarthritis (OA). This is of concern given that global estimates indicate that OA is the fourth leading cause of years lived with disability.1 Moreover, the prevalence and incidence of knee OA, the most common form of this disease, is expected to rise due to the increased life expectancy and consequently aging population. It is therefore possible that health promotion strategies, such as encouragement of physical activity, may inadvertently increase the burden of OA. If promoting physical activity is to continue to be a key, population-wide strategy for the prevention of chronic conditions and the attainment of health benefits, it is important that we understand its effect om weightbearing joints such as the knee.